PERAN KOMISI PENYIARAN INDONESIA (KPI) DAERAH KALIMANTAN TENGAH DALAM PROGRAM LITERASI MEDIA PENYIARAN PADA MAHASISWA KOTA PALANGKA RAYA - Nur Khasanah; Hakim Syah; Nurliana Nurliana; Nisa Rahimia (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
Distorted information and shows tend to damage the nation's identity, radical shows, pornography. and fake news that are easily available to the public have a negative impact on socio culture in society. for this reason, the authorized institution seeks to provide education and learning through the socialization of media literacy programs. in its role and function, the Central Kalimantan Regional Indonesian Broadcasting Commission accommodates aspirations and represents the public's interest in broadcasting. supervise and provide education, with media literacy programs. This research aims to gain understanding and information from the informant's point of view, namely from students, and aims to find out what the duties and functions of the Regional KPI are and how the role of the Central Kalimantan Regional KPI in Broadcasting Media Literacy education to students. by conducting field observations on general knowledge at the Central Kalimantan Regional KPI Institute. Data collection by interview and questionnaire through goggle form. This research received data from two commissioners of PIS field and 10 student informants as well as socialization participants, the research results stated that the role of KPI Central Kalimantan Region is not only supervising but also making efforts to raise awareness to students about critical broadcasting.